STRATEGI KONSERVASI BHISAMA KESUCIAN PURA PADA KAWASAN CAGAR BUDAYA TAMAN NARMADA DALAM MERESPONS PERKEMBANGAN PARIWISATA BUDAYA DI LOMBOK BARAT - Sujana, I Made Putu (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2018)
This research is intended to conduct a study of the strategies of conservation Bhisama the sanctity of the temple which is located in the heritage area in Taman Narmadagarden , Lombok Regency West. The conservation strategies relating to the effort to respond to the development of cultural tourism are relatively rapidly lately. This research is descriptive qualitative research designed in order to give an overview of the three related research focus, i.e. the background history of the Narmada, the management of the Narmada temple and Bhisama conservation strategy the sanctity of Narmada temple. Based on the results of the study found three findings fit the focus of the research. First, the historical background of the existence of the temple which is located in the middle of Narmada Park Reserve Narmada is closely related to the success of the kingdoms of Karangasem organize Government in Lombok. The construction of the Narmada Park by King of Karangasem at the time was as a place to do the rest of the Kings and their families there are some sites that were built during that time are sorted into two, namely, the sacred and the profane. The site which is found to have a level of purity is Kelasa Temple while profane is the garden as a place to do anjangsana (Entertainment). Secondly, manners Narmada temple in conducting religious ritual coordinate with three sub villages namely banjar works dharma bhakti gondawari, banjar jaya presak and youth community (truna banjar) Gondari. In the anniversary ceremony of the activities or ceremonial krama temple along with the coordination banjar third activity and its cost so that it runs successfully. Third, the strategy applied in conducting conservation Bhisma Holiness Temple is doing Setup holy places in accordance with the sanctity of the temple, Bhisma cooperating with related parties, and maintaining the sanctity of the temple by applying rules.